Individuality, as well as genetic background, affects syntactical features of courtship songs in male mice. (October 2021) - Melotti, Luca; Siestrup, Sophie; Peng, Maja; Vitali, Valerio; Dowling, Daniel; von Kortzfleisch, Vanessa Tabea; Bračić, Marko; Sachser, Norbert; Kaiser, Sylvia; Richter, S. Helene
Abstract : Courtship songs in mice have been investigated to understand the mechanisms and ecological relevance of vocal communication. There is evidence that courtship song characteristics vary between individuals from different genetic backgrounds, but little is known about whether individuals, even within the same strain, differ consistently from each other in the syntactical composition and complexity of their songs. In a first confirmatory experiment, we aimed to systematically identify syntactical features typical of songs from different mouse strains, by assessing the composition and complexity (i.e. entropy) of the syntax (i.e. how the different syllables are organized within a song) of male laboratory mice from four different strains ( Mus musculus f. domestica : C57BL/6J, BALB/c, DBA/2 and B6D2F1). Mice were individually presented with a swab containing fresh female urine for 5 min to elicit courtship songs. The four strains differed not only in the composition but also in the complexity of their syntax. In a second experiment, we investigated repeatability over time as a marker of individuality as well as the occurrence of recurring motifs (i.e. identical sets of syllables that are repeated within a song) of BALB/c and DBA/2 mice. The same procedure as in the first experiment was followed, but in addition testing was repeated weekly over 3 weeks. In both strains, most syllable types showed moderate to high repeatability, indicating individuality in song syntax. However, a descriptive hierarchical cluster analysis indicated remarkable variability in how similar the syntaxes of songs from the same individual were over time. Furthermore, individuals varied in the expression of recurring motifs. Our study shows that not only the genetic background but also individuality can affect variability in courtship songs in mice. Together, these findings raise intriguing questions on whether different individual singing strategies exist during courtship. Highlights: Courtship songs in mice can serve as a model to study vocal communication. We assess how strain and individuality affect syntax of courtship songs. Strains differ in composition and also in complexity of song sequences. Most syntactical features are repeatable over time, indicative of individuality. Individuality may partly explain the variation in courtship songs.